Prominent Effects of Berbamine Hydrochloride on Alzheimer’s Disease Model Mice - Chen, Chang-lan; Wang, Hai-li; Qian, Feng; Liu, Mei-hua; Guo, Xiao-xuan; Lv, Jing; Huang, Jia-hui; Zhang, Nai-zhi; Xiang, Zheng (Frontiers in Pharmacology, 2022)
Very few anti-Alzheimer’s disease (AD) drugs are clinically available at present due to the complex mechanism of Alzheimer’s disease. For the purpose of discovering potential anti-AD drugs in bisbenzylisoquinoline alkaloids, the anti-AD function and the mechanism of the function of berbamine hydrochloride (BBMH) were studied. Three kinds of AD model mice, double transgenic APP/PS1 AD mice, Gal-Alu AD mice induced by the intraperitoneal injection of d-galactose combined with the intragastric administration of aluminum trichloride, and Alu AD-like mice induced by stereotactic brain injection of aluminum trichloride, were administered with BBMH for 40 days at a dosage of 280 mg/kg/d. The effects of BBMH on the learning and memory behavior of the AD mice were studied through the Morris water maze experiment, and the influences of BBMH on the pathological features of AD, including the deposition of Aβ, the lesions of pyramidal cells (neurons), and the formation of neurofibrillary tangles, were studied by the immunohistochemical staining, hematoxylin-eosin staining, and silver staining of the brain tissues of the mice. The water maze experiment showed that BBMH could significantly improve the learning and memory abilities of three kinds of treated mice. Immunohistochemical staining showed that BBMH could significantly reduce the deposition of Aβ in the brain tissues of treated mice. Hematoxylin-eosin staining showed that BBMH could significantly alleviate the lesions of pyramidal cells in the hippocampal tissue of the mice. Silver staining showed that BBMH could significantly reduce the formation of neurofibrillary tangles in the hippocampal tissue of the mice. These results indicated that BBMH has significant anti-AD effects and the potential as an anti-AD drug. Western blot analysis of the brain tissue of the mice showed that the expression level of calpain, a Ca2+-dependent proteolytic enzyme, was significantly inhibited and the expression level of SelK, a selenoprotein mainly expressed in immune cells, was significantly increased. It is speculated that the anti-AD effect of BBMH is related to the improvement of the phagocytosis of microglial cells in brain tissues and macrophages migrated into the brain as well as the regulation of calcium homeostasis and calcium-dependent proteases in the brain tissues of the mice.